The moderating role of bank size: influence of fintech, liquidity on financial performance - Sri Hermuningsih; Pristin Prima Sari; Anisya Dewi Rahmawati (Jurnal Siasat Bisnis, 2023)
Purpose – This study aims to examine the impact of fintech, liquidity, and bank size on financial performance in Indonesia's conventional commercial banks registered with the Financial Services Authority. Design/methodology/approach – This study's population consists of Conventional Commercial Banks registered with OJK from 2012 to 2021. The research sample comprises conventional commercial banks using fintech between 2012 and 2021. Purposive sampling was used as a sampling technique. The data from 20 banks with 200 financial statement data show the hypothesis testing using SmartPLS software (PLS-SEM method). Findings– The findings of this study show that fintech has a positive effect on financial performance, bank size is a moderating variable for the repercussions of fintech on financial performance, liquidity also has a positive impact on financial performance, and bank size is a moderating variable for the effectiveness of liquidity on financial performance. Research limitations/implications- The theoretical implication of this research is that a large bank size follows a large liquidity ratio and that the bank's financial performance will tend to be large because the bank can cover its debts easily, which will have an impact on increasing the bank's profit. The greater the growth of Fintech, the better the bank's financial performance. This demonstrates that fintech benefits banks. Banks can increase their profits by implementing fintech. The implications of signaling theory for the effect of bank size on the influence of fintech and liquidity on financial performance. This is due to the public's perception that the information developed by Conventional Commercial Banks and published on the official website is reliable. As a result, people are interested in saving money in conventional commercial banks to improve the bank's financial performance. Practical implications– Provide information and input to investors as a basis for making investment decisions related to variables that affect financial performance, especially in Conventional Commercial Banks. Originality/value – This study fills the gap from previous research that is still inconclusive on the factors that affect financial performance. The novelty in this study is that bank size is used as a moderating variable to analyze whether bank size strengthens or weakens the relationship between financial technology, liquidity, and financial performance at Conventional Commercial Banks.